Model Psikoedukasi untuk Meningkatkan Pemahaman dan Efikasi Diri Penderita Diabetes Mellitus Tipe2 - Nailiy Huzaimah (Wiraraja Medika : Jurnal Kesehatan, 2018)
Health education is one part of type 2 diabetes mellitus (T2DM) management. Healtheducation on T2DM has been given to patients with T2DM but has not resulted in positivebehavioral changes, seen from uncontrolled blood glucose levels and complications. Acomprehensive knowledge of T2DM, appropiate education with engaging families, can give apositive impact on comprehension and self-confidence of people with T2DM.The purpose of this study was to determine the effect of PsychoeducationMods (PM) on comprehension and self-efficacy patients with T2DM. This study uses quasyexperiment, pre and post test control group design. Respondents were patients with T2DM andtheir families who are undergoing outpatient in Dr. H. Moh. Anwar Sumenep Hospital (n = 40).Data collection used a comprehension and self-efficacy questionnaires for people withT2DM. Statistical analysis used different test with α <0,05. Mann Whitney U test result showed thatthere were differences in comprehension and self-efficacy variables between treatment group andcontrol group. Different independent sample test results in the treatment group using Paired Ttest and Wilcoxon signed rank test showed that PM improves comprehension (p = 0.007) and selfefficacy (p = 0.002) of patients with T2DM. MP needs to be applied by health personnel, especiallynurses in assisting patients with T2DM improves comprehension with the awareness and selfefficacy of patients with T2DM. Comprehension with awareness and good self efficacy with familysupport will be a reinforcing factor for the establishment of a positive behavior to control bloodglucose levels.